Characterization of the complete chloroplast genome of Lycium ruthenicum (Solanaceae) - Gulbar Yisilam; Reyim Mamut; Jin Li; Pan Li; Chengxin Fu (Mitochondrial DNA. Part B. Resources, 2018)
Lycium ruthenicum is a precious desert plant with high medicinal and ecological values. It contains rich anthocyanins, which are safe natural pigments and could be used for natural food colorants. In this study, the complete chloroplast (cp) genome of L. ruthenicum was assembled on the basis of next generation sequencing. The whole genome is 154,996 bp in length, including two single copy regions (LSC: 85,993 bp and SSC: 18,213 bp) and two inverted repeat regions (IR: 25,395 bp). The overall G + C content of the genome is 37.9%. The cp genome consists of 111 unique genes, including 30 tRNA genes, 4 rRNA genes and 77 protein-coding genes. Phylogenetic analysis indicates that L. ruthenicum is closely clustered with Atropa belladonna, Przewalskia tangutica, and Scopolia parviflora.